architecture from 'France pittoresque, ou description... des... - Auteur inconnu... (The British Library)
Notice issue d Europeana. This image has been taken from scan 000584 from volume 02 of "France pittoresque, ou description... des departements et colonies de la France, etc. [With plates.]". The title and subject terms of this image have been generated from tags, created by users of the British Library's flickr photostream.
http://creativecommons.org/publicdomain/mark/1.0/
Keywords: europeana; image; patrimoine europeen; Bibliothèque numerique; iconographie